2007
DOI: 10.1128/iai.01879-06
|View full text |Cite
|
Sign up to set email alerts
|

Priming with an Adenovirus 35-Circumsporozoite Protein (CS) Vaccine followed by RTS,S/AS01B Boosting Significantly Improves Immunogenicity toPlasmodium falciparumCS Compared to That with Either Malaria Vaccine Alone

Abstract: The RTS,S/AS02A protein-based vaccine consistently demonstrates significant protection against infection with Plasmodium falciparum malaria and also against clinical malaria and severe disease in children in areas of endemicity. Here we demonstrate with rhesus macaques that priming with a replication-defective human adenovirus serotype 35 (Ad35) vector encoding circumsporozoite protein (CS) (Ad35.CS), followed by boosting with RTS,S in an improved MPL-and QS21-based adjuvant formulation, AS01B, maintains antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
71
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(76 citation statements)
references
References 40 publications
(50 reference statements)
4
71
1
Order By: Relevance
“…This represents an important test of the adenovirus-protein and adenovirus-MVA-protein regimens in macaques, prior to evaluation of these promising regimens in clinical trials. Further studies will be needed to compare the titers induced by vector-protein regimens with protein-only regimens in macaques, although other murine and macaque vaccine studies with different constructs have suggested that they may perform comparably (34,37). Interestingly, boosting with protein formulated in CoVaccine HT only led to moderately higher-peak and long-term IgG titers in comparison with formulation in Alhydrogel.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This represents an important test of the adenovirus-protein and adenovirus-MVA-protein regimens in macaques, prior to evaluation of these promising regimens in clinical trials. Further studies will be needed to compare the titers induced by vector-protein regimens with protein-only regimens in macaques, although other murine and macaque vaccine studies with different constructs have suggested that they may perform comparably (34,37). Interestingly, boosting with protein formulated in CoVaccine HT only led to moderately higher-peak and long-term IgG titers in comparison with formulation in Alhydrogel.…”
Section: Discussionmentioning
confidence: 99%
“…These murine studies also described further possible advantages of viral vectors in achieving consistent Ab priming, enhanced Ab avidity, and Th1-type IgG isotype skew. Data from the HIV-1 (32-36) and liver-stage malaria vaccine fields (37,38) also encourage efforts to combine adenoviral-vectored vaccines with protein vaccines.…”
mentioning
confidence: 99%
“…This observation was corroborated by the results obtained in the ELISPOT assay and with pentamer staining. A difference in the effect of Ad35 when used as a priming or a boosting vaccine has been indicated in an earlier study in which prime-boost immunizations of nonhuman primates with rAd35.CS and adjuvanted RTS,S protein were performed (56). Although the complete sequences of the antigen expressed by the rAd35 vector and the adjuvanted protein were not completely matching (N-terminal truncation in the protein), the study showed that rAd35 priming/protein boosting was a superior regimen for inducing IFN-␥-producing CD4 ϩ T cells.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated recently in a nonhuman primate study that a prime-boost immunization regimen combining the rAd35 vector coding for the Plasmodium falciparum circumsporozoite (CS) protein and adjuvanted RTS,S was superior to either modality alone in the induction of T-cell immunity (56). In the current study, we investigated whether this effect can be extended to other Plasmodium falciparum antigens, in particular to liver-stage antigen 1 (LSA-1).…”
mentioning
confidence: 98%
“…Combining RTS,S with a viral vector expressing either CS protein or other appropriate sporozoite or liver-stage Ags in a prime and boost regimen could induce both strong Ab and CD4 and CD8 T cell responses leading to more durable protection [71]. In support, a study in macaques demonstrated that two doses of RTS,S following an adenovirus 35 CS-protein priming immunization retained the RTS,S-induced Ab response while promoting a markedly higher CD4 T-cell response that remained elevated for about 2 months [72].…”
Section: Discussionmentioning
confidence: 54%